2004
DOI: 10.2117/psysoc.2004.35
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Phonological Loop in Task Switching Performance: The Effect of Articulatory Suppression in the Alternating Runs Paradigm

Abstract: We examined the role of the phonological loop in task switching performance in a prevalently used research paradigm, that is, the alternating runs paradigm. This paradigm basically requires participants to alternate tasks on every second trial (i.e., AABBAABB). In this study, participants were required to alternate the letter and numerical decision tasks in cue-present and cue-absent conditions under control, articulatory suppression and foot tapping conditions. The results showed that error rates were larger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
16
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 9 publications
(16 reference statements)
5
16
0
Order By: Relevance
“…They suggested that a critical function of verbalization is the endogenous sequencing of tasks on the basis of the sequential characteristics of language. In keeping with earlier arguments presented by Saeki and Saito (2004b), Bryck and Mayr also indicated that articulatory suppression does not interfere with the process of switching between tasks; instead, verbalization plays a critical role in the control of the serial order of tasks.…”
supporting
confidence: 76%
See 4 more Smart Citations
“…They suggested that a critical function of verbalization is the endogenous sequencing of tasks on the basis of the sequential characteristics of language. In keeping with earlier arguments presented by Saeki and Saito (2004b), Bryck and Mayr also indicated that articulatory suppression does not interfere with the process of switching between tasks; instead, verbalization plays a critical role in the control of the serial order of tasks.…”
supporting
confidence: 76%
“…Verbal representations likely underpin the process of sequential task decision, and articulatory suppression in the predictable and sequential task-switching paradigms might interfere with participants completed pure-task blocks, in which they performed only one task (i.e., only the parity task or only the magnitude task). Because previous studies had suggested that articulatory suppression increases the mixing cost but not the switch cost (Bryck & Mayr, 2005;Saeki & Saito, 2004b), we predicted the same pattern of results if articulatory suppression had an effect on task performance.…”
mentioning
confidence: 67%
See 3 more Smart Citations